Pengaruh Literasi Keuangan dan Green Perceived Risk terhadap Keputusan Investasi Milenial Jawa Barat - Manggala Putra Halim; Rindang Matoati; Eka Dasra Viana; Rindah Febriana Suryawati (IPB University, 2022)
An increasing number of young investors have an important role in supporting the economy. However, increasing the number of investors does not mean much if the investment decisions made are not right, so it needs to be supported by an understanding of good finance. Stocks offer opportunities to get a higher return, with a higher risk as well. Stocks have varying levels of risk, such as companies that carry out sustainable business practices will differ from companies that do not, so perceived risk can influence investor’s investment decisions. Therefore, this study aims to identify the effect of financial literacy and green perceived risk on millennial generation investment decisions on the SRI-KEHATI stock index. Data analysis used descriptive analysis and PLS Structural Equation Modeling (SEM) analysis. The results showed there was a significant positive influence of financial literacy to investment decisions, which means that the better the literacy the better the decision. Green perceived risk has a significant negative effect on investment decisions, which means the greater the risk of environmental damage, the less likely it to invest in the SRI-KEHATI stock index.